SOME ASPECTS OF INTERNATIONALIZATION OF HIGHER EDUCATION (illustrated on the example of FRG [Federal Republic of Germany] and the Republic of Turkey) - G. M. Mukhambetkaliyeva; U. M. Mukhambetkali (Scientific Journal of Pedagogy and Economics, 2019)
The article is devoted to a comparative analysis of the development of international cooperation in the area of higher education carried out by German and Turkish universities, its strategic planning, measures for its implementation and the results achieved. Based on the experience of two countries in organizing cooperation in education at all levels of its acceptance, the article presents the existing aspects of the internationalization of education. It is noted that the internationalization of higher education through the implementation of joint educational projects contributes not only to improving the quality of education, but also to establishing social and cultural, economic and business contracts between countries, and assists in maintaining and strengthening of interactions between the peoples of the world. The purpose of this paper abstract is to study the multidimensionality of integration processes in higher education. The growing interconnection and interdependence of the countries and peoples of the modern world, the internationalization of education, science, economics and culture, the exacerbation of global problems that cannot be resolved without going beyond the national framework and state borders - all this makes it extremely important to study world experience in various areas of public life and scientific knowledge areas.